Study On The Effects Of Catharanthus Roseus-silver Nanoparticles On Human Hepatocellular Carcinoma Cell Line Hepg2 - Azhar, Nur Asna (2024)
Cancer is a major global health challenge that continues to increase worldwide, posing a significant obstacle to achieving long life expectancy. Conventional chemotherapy drugs may not be specific enough, leading to significant side effects and harm to healthy cells. Therefore, alternative cancer therapies are crucial, and application of silver nanoparticles (AgNPs) presents a novel approach to cancer treatment due to their unique features. Utilising plants for the biosynthesis of AgNPs offers several advantages over other methods. Numerous studies had reported that plant mediated AgNPs synthesis have been found to exhibit potent anticancer activity against various cancer cell lines. Thus, the antiproliferative effects and selective index (SI) of Catharanthus roseus-silver nanoparticles (C. roseus-AgNPs) on hepatocellular carcinoma (HepG2) cells were determined by using normal liver cell line (THLE-3) as a control. C. roseus-AgNPs was more potent than C. roseus-aqueous extract in inhibiting the proliferation of HepG2 cells while exhibiting less inhibition towards THLE-3 cells. C. roseus-AgNPs demonstrated selective toxicity towards HepG2 cells with a high SI value (>2) compared to camptothecin. For both C. roseus-AgNPs and C. roseus-aqueous extract treatments, several apoptotic features were detected when observed using IncuCyte live-cell analysis system, including cell shrinkage, rounded cells, and retracted. The underlying mechanisms associated with the inhibitory effects in the treated cells were further explored.